Interne und externe Stabilität - Bodo Steinmann (Kredit und Kapital, 1970)
Internal and External Stability A critical appraisal of proposals by R. A. Mundell and W. Stützel This article ventilates proposals by Mundell and Stützel who recommend that, in overall economic situations in which objectives of internal and external stability conflict with each other within the framework of the prevailing international economic system, the instruments of economic policy should be split up. Fiscal policy should be expansive (contractive) to attain full employment coupled with monetary stability, while monetary policy - simultaneously contractive (expansive) - should serve to square the balance of payments. It proves, however, that the investigated proposals cannot - as intended - solve the dilemma with which many countries are faced in trying to achieve internal and external economic goals simultaneously without sacrificing the priority of one of the goals or having to veer off the course of the existing international monetary system. A consideration of the three levels on which the means applied may conflict with each other in achieving objectives (mutual impairment in application, in effectiveness and, finally, in consequence of the degree of attainment of goals) shows that the splitting up of economic policy instruments can constitute a solution - though to different extents according to the two authors - at best for the first two. Experience will show that if economic policy achieves one of the conflicting objectives, it will render attainment of the other more difficult, despite the splitting up of economic policy instruments.
Keywords: 330